(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Infertility is a global health issue affecting approximately 8-10% of couples and has multidimensional problem with social, economic and cultural implications, which can take threatening proportions in countries with strong demographic problems. Objective: To investigate the determinants of infertility among couples seeking treatment. Methodology: A cross sectional study was conducted in selected private clinic of Dhaka city among 196 infertile couple by face to face interview using pretested semi structured questionnaire. Results: The sample studied consisted of 196 infertile couple. One third (38%) aged 26-30 years, majority Muslims (96%), housewives (72%) and one fourth (24%) had education level of secondary to higher secondary. Slightly more than half of their family income was taka 5361-21270. More than three fourth (66%) had primary infertility. Concerning the determinants of infertility polycystic ovary, hormonal imbalance, and fallopian tube blockage was 19%, 16% and 7% respectively but unexplained factors (28%) crossed the other factors. Only male factor was 10% and combined male and female factors were 10% among study subjects. Regarding the daily habits of the male participants, 18% were smokers. Conclusions: The determinants of female infertility are problems in the fallopian tubes and the uterus, disorders of menstruation, sexual disorders, age and ovarian failure. Female infertility is a complex problem that should be considered carefully by the government and stakeholders in each country in order to find effective interventions and solutions. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21021